Research Progress on Combined Remediation Technologies and Applications for Petroleum⁃Contaminated Soils - Hailin MA; Zhiping FAN; Bo WANG; Siyu WANG; Chengjie SUN (Liaoning Shiyou Huagong Daxue xuebao, 2025)
In the process of oil exploitation, processing, storage and transportation, the total petroleum hydrocarbon (TPH) released into the soil not only changes the physical and chemical properties of the soil, but also seriously affects the quality of the water environment through the process of migration and transformation. Addressing the environmental issue of petroleum⁃contaminated soils, the development of efficient, green, and environmentally friendly remediation technologies has become a critical need in the industry. This paper reviews the main remediation technologies for petroleum⁃contaminated soils based on current domestic and international research. The study showed that physical methods are suitable for remediating soils contaminated with highly volatile and highly permeable petroleum, chemical methods are appropriate for treating severely and recalcitrantly contaminated soils, and biological methods are more environmentally friendly and better suited for treating mildly contaminated soils. By comparing the principles and application ranges of different remediation technologies, it is evident that combined remediation technologies offer strong versatility and widespread applicability. This paper also explores future trends in the development of green and environmentally friendly remediation technologies for petroleum⁃contaminated soils, aiming to provide a reference for practical applications in soil remediation.